Influence of refining slag composition on nonmetallic inclusions in 38CrMoAl steel - Guofang Xu; Shiheng Liang; Bo Song; Wei Liu; Shufeng Yang; Li Zhao; Yabing Zhang (Journal of Materials Research and Technology)
To achieve economic transfer of calcium and accurate inclusion modification by utilizing the high basicity of slag instead of calcium treatment, the refining slag of 38CrMoAl steel was optimized through thermodynamic calculations in view of the large size and high melting point of nonmetallic inclusions that occur during the production of the steel grade in the refining process of a domestic plant. The inclusions lead to severe nozzle clogging and affect the quality of the molten steel. An industrial experiment was subsequently conducted to verify the results. The optimized refining slag (57.5% CaO, 23% Al2O3, 3% MgO and 5% SiO2) was beneficial for inclusion removal at 1600 °C, and the actual refining slag (58.5% CaO, 27.5% Al2O3, 3% MgO and 1.41% SiO2) was very close to the optimized slag. The morphology and composition of nonmetallic inclusions in different processes were analysed via SEM, and the number and size of nonmetallic inclusions in different processes of LF were also analysed. The results indicate that the size of nonmetallic inclusions after the refining slag is optimized is smaller than before, especially after aluminium is fed into the LF. The type of nonmetallic inclusions changed, and the diameter and number density of the nonmetallic inclusions decreased. The highest proportion of inclusions in the nozzle clog also changed. The number of heats for the continuous pouring of the tundish increased from 6 to 12.